Peningkatan Kompetensi Guru dalam Pengembangan RPP Kurikulum 2013 Melalui Asistensi di MAN Pugaan Tahun 2016 - Nana Mairi Mairi (Jurnal PTK dan Pendidikan, 2018)
Learning planning is incorporated into the Lesson Plans (RPP) or some other terms such as instructional design, learning scenarios. RPP contains KI, KD, indicators to be achieved, materials to be learned, learning steps, learning media, and learning resources and assessment. Problems that happened many teachers who have not understood and motivated in preparing the Curriculum Learning Implementation Plan 2013 completely. Most teachers did not received training in curriculum development in 2013. This research aims to improve teacher competence in preparing the Learning Implementation Plan through assistance in MAN Pugaan (KabupatenTabalong). Method used in this research is School Action Research that conducted through two cycles. Subjects are teachers of MAN Pugaan amounted to 27 teachers of civil servants and non-civil servants. The results is in cycle I the mean value of RPP component was 69% and in cycle II 83%. So, there was an increase of 14% from cycle I.